Charged ligand post-modified photocatalyst as well as preparation method and application thereof
By encapsulating metal nanoparticles in Zr-BTB support and modifying them with quaternary ammonium salt small molecules, the problem of agglomeration and inactivation of photocatalysts in the reaction is solved, the hydrogen production efficiency and stability of the photocatalysts are improved, and efficient photocatalysts are achieved Catalytic reaction.
Patent Information
- Application Number
- CN202411374762.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
AI Technical Summary
The agglomeration and inactivation of metal nanoparticles in photocatalytic reactions leads to low catalyst stability and efficiency, limiting the improvement of photocatalytic efficiency.
By uniformly encapsulating metal nanoparticles in the Zr-BTB support and modifying quaternary ammonium salt small molecules through coordination bond grafting, proton relay and electron hole separation are achieved, thereby improving the electron migration efficiency and surface reaction rate of the catalyst.
The hydrogen production efficiency of the photocatalyst is significantly improved, reaching more than 4000μmol g−1h−1, and can exceed 10000μmol g−1h−1, improving the stability and reaction efficiency of the catalyst.
Smart Images

Figure CN119237019A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photocatalysis, and particularly relates to a charged ligand post-modified photocatalytic material and a preparation method and application thereof. Background Art
[0002] As a recognized clean energy, hydrogen energy has the characteristics of light weight, high energy density, zero pollution and zero carbon emissions. In particular, the characteristics of zero pollution and zero emissions are highly consistent with the current urgent global demand for green and sustainable development. Solar-driven photocatalytic hydrogen production is considered to be a feasible means to solve the energy crisis and environmental problems.
[0003] However, despite the broad prospects of photocatalytic hydrogen production technology, its practical application still faces many challenges, among which the most core and urgent ones are the in-depth understanding of the photocatalytic reaction mechanism and the improvement of efficiency. At present, the specific mechanisms of key links such as the absorption of photons, the generation and separation of electron-hole pairs, and the subsequent surface catalytic reaction in the photocatalytic process have not been fully clarified, which directly limits the further improvement of photocatalytic efficiency. In addition, although traditional bulk photocatalytic materials have stable structures, they often have low atomic utilization and unsatisfactory energy conversion efficiency due to problems such as small specific surface area, poor light absorption capacity, and low electron migration efficiency, resulting in a large waste of precious solar energy resources.
[0004] On the other hand, metal nanoparticles, with their unique surface effects and quantum size effects, show extremely high catalytic activity, providing new possibilities for improving photocatalytic efficiency. However, due to their extremely high surface energy, these nanoparticles are prone to agglomeration during the reaction, which not only greatly reduces their effective catalytic area, but also may cause active sites to be shielded, thereby rapidly deactivating the catalyst, seriously affecting the stability and sustainability of the catalytic reaction.
[0005] Therefore, improving the efficiency of artificial photocatalysts and developing new photocatalytic materials are the core issues facing this field. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a photocatalytic material modified with charged ligands and its preparation method and application, which solves the problem of agglomeration and deactivation of metal nanoparticles as catalytic active centers during the reaction process.
[0007] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for preparing a photocatalyst modified with a charged ligand, comprising: Add Zr-BTB, potassium chloroplatinite solution and deionized water into ethanol and mix them evenly to react. After the reaction is completed, Zr-BTB@Pt is obtained. Zr-BTB@Pt and quaternary ammonium salt ligands were dispersed in methanol and reacted to obtain Zr-BTB@Pt-NH4 + .
[0008] The mass ratio of the Zr-BTB, potassium chloroplatinite and deionized water is 15:(3-9):1000.
[0009] The mass ratio of the Zr-BTB@Pt and the quaternary ammonium salt ligand is 1:(6~10).
[0010] The Zr-BTB is added to the ethanol, the potassium chloroplatinite solution and the deionized water are mixed evenly to react, and Zr-BTB@Pt is obtained after the reaction is completed. Specifically, Zr-BTB, potassium chloroplatinite solution and deionized water were added to ethanol, and ultrasonic treatment was performed for 30 to 60 minutes to obtain a first product. The first product was washed with deionized water and ethanol and then dried to obtain Zr-BTB@Pt.
[0011] The Zr-BTB@Pt and the quaternary ammonium salt ligand are dispersed in methanol and reacted to obtain Zr-BTB@Pt-NH4 + , specifically: Zr-BTB@Pt and quaternary ammonium salt ligands were dispersed in methanol and condensed under reflux for 12 to 16 hours to obtain a second product, which was washed with methanol and dried to obtain Zr-BTB@Pt-NH4 + .
[0012] The preparation method of the Zr-BTB is specifically as follows: The zirconium salt and 1,3,5-tri(4-carboxyphenyl)benzene are dissolved in N,N-dimethylformamide, and then formic acid and water are added to the N,N-dimethylformamide, and ultrasonic dispersion is performed to obtain a dispersion, and the dispersion is heated to obtain a third product. After cooling to room temperature, the third product is washed with N,N-dimethylformamide and ethanol, and then dried to obtain Zr-BTB.
[0013] The zirconium salt includes zirconium chloride and anhydrous zirconium oxychloride; the mass ratio of the zirconium salt to 1,3,5-tris(4-carboxyphenyl)benzene is 1:(1-1.5); The heating condition is to keep the temperature in an oven at 110° C. to 130° C. for 48 to 60 hours.
[0014] The quaternary ammonium salt ligand is prepared by the following method: Dissolve isonicotinic acid and methyl iodide in methanol, condense and reflux for 40 to 48 hours, cool to room temperature, filter to obtain a red solid, wash with acetone until the solid turns yellow, and then recrystallize with methanol to obtain a quaternary ammonium salt ligand; The mass ratio of isonicotinic acid to methyl iodide is 3:(5-6).
[0015] The present invention also provides a photocatalyst with a charged ligand post-modified prepared according to the above preparation method.
[0016] The present invention also provides the use of the above-mentioned charged ligand post-modified photocatalyst in photocatalytic hydrogen production.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The invention provides a method for preparing a photocatalytic material modified with a charged ligand. The invention takes Zr-BTB as a model, uniformly encapsulates metal nanoparticles in a Zr-BTB carrier, and solves the problem of agglomeration and deactivation of the metal nanoparticles as catalytic active centers during a reaction by a carrier encapsulation method; then, a quaternary ammonium salt small molecule is grafted onto the unsaturated Zr cluster in a coordination bond manner, and the charged characteristics of the quaternary ammonium salt small molecule are utilized to realize proton relay so as to accelerate the electron-hole separation efficiency during the photocatalytic process. Meanwhile, the quaternary ammonium salt small molecule can also realize a substrate activation process in a surface reaction to further improve the photocatalytic hydrogen production efficiency.
[0018] The charged ligand post-modified photocatalytic material provided by the present invention uniformly encapsulates metal nanoparticles in a Zr-BTB carrier, and then modifies the Zr-BTB carrier with a quaternary ammonium salt ligand, which can greatly improve the electron-hole separation process during the photocatalytic reaction and improve the photocatalytic efficiency of the photocatalyst.
[0019] The photocatalyst prepared by the present invention is used for catalytic reaction, and the hydrogen production efficiency can reach 4000 μmol g −1 h −1 The maximum hydrogen production efficiency can exceed 10000 μmol g −1 h −1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for use in the embodiment: Figure 1 Zr-BTB@Pt-NH4 prepared in Example 1 + Transmission electron microscope images of Figure 2 Zr-BTB@Pt-NH4 prepared in Example 1 + Comparison of the photocatalytic hydrogen production efficiency of Zr-BTB@Pt prepared in Comparative Example 1; Figure 3 Zr-BTB@Pt-NH4 prepared in Example 2-6 + Comparison of photocatalytic hydrogen production efficiency. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] At present, metal organic frameworks (MOFs) have attracted wide attention in the fields of biomedicine, chemical sensing, catalysis, etc. Metal organic frameworks are a type of porous crystalline materials composed of metal nodes and organic ligands bridged by coordination bonds. In particular, they have clear structures, adjustable pore environments, and flexible and changeable compositions, which can achieve precision at the atomic scale. They are good models for studying the structure-activity relationship of chemical reactions. At the same time, MOFs also have semiconductor properties. Through their confined active metal nanoparticles, they can effectively alleviate the problem of inactivation of active centers due to agglomeration. At the same time, through the reasonable modification of MOFs, the electron-hole separation process in the photocatalytic reaction can be greatly improved, thereby improving the photocatalytic efficiency.
[0023] The present invention provides a method for preparing a photocatalytic material with a charged ligand post-modification, comprising the following steps: Add Zr-BTB, potassium chloroplatinite solution and deionized water to ethanol, disperse evenly and react to obtain gray-black powder, which is recorded as Zr-BTB@Pt; Zr-BTB@Pt and quaternary ammonium salt ligands were added to methanol to react and obtain powder, which was recorded as Zr-BTB@Pt-NH4 + .
[0024] The present invention is further explained below: In some embodiments, the mass ratio of Zr-BTB, potassium chloroplatinite and deionized water is 15: (3-9): 1000. It should be noted that when the Pt loading is at a high level, there will be a shielding effect between the Pt nanoparticles, and the atomic utilization rate will decrease, resulting in the catalytic activity not being able to increase linearly.
[0025] In some embodiments, the mass ratio of Zr-BTB@Pt to the quaternary ammonium salt ligand is 1:(6-10). It should be noted that due to the limited coordination capacity of the unsaturated Zr clusters in Zr-BTB, when this ratio is exceeded, the ligand cannot be grafted onto the Zr-BTB carrier even if the amount of the ligand is increased after full coordination.
[0026] In some embodiments, Zr-BTB, potassium chloroplatinite solution and deionized water are added to ethanol, and ultrasonic treatment is performed for 30 to 60 minutes to obtain a first product, and the first product is washed with deionized water and ethanol, and then dried to obtain Zr-BTB@Pt, which is gray-black. In the process of preparing Zr-BTB@Pt, platinum ions in potassium chloroplatinite are reduced to platinum nanoparticles under the action of deionized water, and then the platinum nanoparticles are fixed to the Zr-BTB carrier to prevent the catalyst from reducing its activity due to agglomeration or shedding of nanoparticles during use, thereby improving the stability of the catalyst.
[0027] In some embodiments, Zr-BTB@Pt and quaternary ammonium salt ligands are dispersed in methanol, condensed and refluxed for 12 to 16 hours, and then cooled to room temperature to obtain a second product, which is then washed with methanol and dried to obtain Zr-BTB@Pt-NH4+. Preparation of Zr-BTB@Pt-NH4 + During the reaction, the reaction temperature is controlled by a condensation reflux process, so that the quaternary ammonium salt ligand is grafted onto the unsaturated Zr clusters of the Zr-BTB carrier.
[0028] The preparation method of the Zr-BTB is specifically as follows: The zirconium salt and 1,3,5-tri(4-carboxyphenyl)benzene are dissolved in N,N-dimethylformamide (DMF), and then formic acid and water are added to N,N-dimethylformamide, and ultrasonic dispersion is performed to obtain a dispersion. The dispersion is sealed and placed in an oven at 110°C to 130°C for 48 to 60 hours. After cooling to room temperature, it is washed with DMF and ethanol for 1 to 3 times respectively and then dried to obtain a white powder, which is recorded as Zr-BTB.
[0029] In some embodiments, the zirconium salt includes zirconium chloride and anhydrous zirconium oxychloride; the mass ratio of the zirconium salt to 1,3,5-tri(4-carboxyphenyl)benzene is 1:(1-1.5); and the mass ratio of formic acid to water is (2-3):1.
[0030] It should be noted that the Zr-BTB carrier prepared by the method for preparing the Zr-BTB carrier provided by the present invention has a regular porosity and a large specific surface area, as well as excellent stability.
[0031] In some embodiments, the preparation method of the quaternary ammonium salt ligand is specifically: Dissolve isonicotinic acid and iodomethane in methanol, condense and reflux for 40 to 48 hours, cool to room temperature, filter to obtain a red solid, wash with acetone until the red solid turns yellow, and then recrystallize and purify with methanol to obtain a quaternary ammonium salt ligand, which is a yellow crystal.
[0032] In some embodiments, the mass ratio of isonicotinic acid to methyl iodide is 3:(5-6).
[0033] It should be noted that the quaternary ammonium salt ligand prepared by the method for preparing the quaternary ammonium salt ligand provided by the present invention has good thermal stability and chemical stability, so that the quaternary ammonium salt ligand can maintain the stability of its structure and performance in subsequent applications.
[0034] In the following examples, unless otherwise specified, all materials used can be obtained through common channels; and the test methods adopted are conventional methods in the art.
[0035] Example 1 Zr-BTB: Dissolve 10 mg ZrCl4 and 10 mg 1,3,5-tri(4-carboxyphenyl)benzene in 3 ml N,N-dimethylformamide, then add 1 ml formic acid and 0.5 ml deionized water, and disperse evenly by ultrasonication to obtain a dispersion. Seal the dispersion and place it in an oven at 120°C for 48 hours. After cooling to room temperature, wash it twice with DMF, wash it once with ethanol, and then dry it to obtain a white powder, recorded as Zr-BTB.
[0036] Zr-BTB@Pt: Weigh 15 mg of Zr-BTB and disperse it in 5 ml of ethanol. Add 300 μl of 10 mg / ml potassium chloroplatinite solution and 1 ml of deionized water and ultrasonically treat for 40 minutes. Then wash with deionized water and ethanol and dry to obtain a gray-black powder recorded as Zr-BTB@Pt.
[0037] Quaternary ammonium salt ligand: 15 g of isonicotinic acid and 26 g of methyl iodide were dissolved in 70 ml of methanol, and the mixture was cooled to room temperature after condensation reflux treatment for 40 hours. A red solid was obtained by filtration, and the red solid was washed with acetone until it turned yellow. The quaternary ammonium salt ligand was then purified by recrystallization with methanol. The quaternary ammonium salt ligand was yellow crystals.
[0038] Zr-BTB@Pt-NH4 + : 10 mg Zr-BTB@Pt and 60 mg quaternary ammonium salt ligand were dispersed in 10 ml methanol, condensed and refluxed for 12 hours, cooled to room temperature, washed with methanol and dried to obtain a powder named Zr-BTB@Pt-NH4 + . Zr-BTB@Pt-NH4 + The transmission electron microscopy is as follows Figure 1As shown in Figure 2, it can be seen that Pt nanoparticles are evenly distributed on the two-dimensional Zr-BTB, and the size of the nanoparticles is between 2.0 and 3.5 nanometers.
[0039] Embodiment 2: Zr-BTB: Dissolve 10 mg ZrCl4 and 10 mg 1,3,5-tri(4-carboxyphenyl)benzene in 3 ml N,N-dimethylformamide, then add 1 ml formic acid and 0.5 ml deionized water, and disperse evenly by ultrasonication to obtain a dispersion. Seal the dispersion and place it in an oven at 120°C for 48 hours. After cooling to room temperature, wash it twice with DMF, wash it once with ethanol, and then dry it to obtain a white powder, recorded as Zr-BTB.
[0040] Zr-BTB@Pt: Weigh 15 mg of Zr-BTB and disperse it in 5 ml of ethanol. Add 600 μl of 10 mg / ml potassium chloroplatinite solution and 1 ml of deionized water and ultrasonically treat for 60 minutes. Then wash with deionized water and ethanol and dry to obtain a gray-black powder recorded as Zr-BTB@Pt.
[0041] Quaternary ammonium salt ligand: 15 g of isonicotinic acid and 26 g of methyl iodide are dissolved in 70 ml of methanol, and the mixture is cooled to room temperature after condensation reflux for 48 hours. A red solid is obtained by filtration, and the solid is washed with acetone until it turns yellow. The quaternary ammonium salt ligand is then purified by recrystallization with methanol. The quaternary ammonium salt ligand is yellow crystals.
[0042] Zr-BTB@Pt-NH4 + : 10 mg Zr-BTB@Pt and 60 mg quaternary ammonium salt ligand were dispersed in 10 ml methanol, condensed and refluxed for 12 hours, cooled to room temperature, washed with methanol and dried to obtain a powder named Zr-BTB@Pt-NH4 + -2.
[0043] Embodiment 3: Zr-BTB: Dissolve 10 mg of anhydrous zirconium oxychloride and 12 mg of 1,3,5-tri(4-carboxyphenyl)benzene in 3 ml of N,N-dimethylformamide, then add 1 ml of formic acid and 0.5 ml of deionized water, and disperse evenly by ultrasonication to obtain a dispersion. Seal the dispersion and place it in an oven at 110°C for 55 hours. After cooling to room temperature, wash it twice with DMF, wash it once with ethanol, and then dry it to obtain a white powder, recorded as Zr-BTB.
[0044] Zr-BTB@Pt: Weigh 15 mg of Zr-BTB and disperse it in 5 ml of ethanol. Add 900 μl of 10 mg / ml potassium chloroplatinite solution and 1 ml of deionized water and ultrasonically treat for 40 minutes. Then wash with deionized water and ethanol and dry to obtain a gray-black powder recorded as Zr-BTB@Pt.
[0045] Quaternary ammonium salt ligand: 15 g of isonicotinic acid and 26 g of methyl iodide were dissolved in 70 ml of methanol, and the mixture was cooled to room temperature after condensation reflux for 40 hours. A red solid was obtained by filtration, and the solid was washed with acetone until it turned yellow. The quaternary ammonium salt ligand was purified by recrystallization with methanol. The quaternary ammonium salt ligand was yellow crystals.
[0046] Zr-BTB@Pt-NH4 + : 10 mg Zr-BTB@Pt and 60 mg quaternary ammonium salt ligand were dispersed in 10 ml methanol, condensed and refluxed for 13 hours, cooled to room temperature, washed and dried with methanol, and the obtained powder was recorded as Zr-BTB@Pt-NH4 + -3.
[0047] Embodiment 4: Zr-BTB: Dissolve 10 mg ZrCl4 and 10 mg 1,3,5-tri(4-carboxyphenyl)benzene in 3 ml N,N-dimethylformamide, then add 1 ml formic acid and 0.5 ml deionized water, and disperse evenly by ultrasonication to obtain a dispersion. Seal the dispersion and place it in an oven at 110°C for 60 hours. After cooling to room temperature, wash it twice with DMF, wash it once with ethanol, and then dry it to obtain a white powder, recorded as Zr-BTB.
[0048] Zr-BTB@Pt: Weigh 15 mg of Zr-BTB and disperse it in 5 ml of ethanol. Add 300 μl of 10 mg / ml potassium chloroplatinite solution and 1 ml of deionized water and ultrasonically treat for 40 minutes. Then wash with deionized water and ethanol and dry to obtain a gray-black powder recorded as Zr-BTB@Pt.
[0049] Quaternary ammonium salt ligand: Dissolve 15 g of isonicotinic acid and 26 g of methyl iodide in 70 ml of methanol, reflux by condensation for 46 hours, then cool to room temperature, filter to obtain a red solid, wash with acetone until the red solid turns yellow, and then recrystallize and purify with methanol to obtain a quaternary ammonium salt ligand, which appears as yellow crystals.
[0050] Zr-BTB@Pt-NH4 + : 10 mg Zr-BTB@Pt and 80 mg quaternary ammonium salt ligand were dispersed in 10 ml methanol, condensed and refluxed for 16 hours, cooled to room temperature, washed with methanol and dried to obtain a powder named Zr-BTB@Pt-NH4 + -4.
[0051] Embodiment 5: Zr-BTB: Dissolve 10 mg ZrCl4 and 10 mg 1,3,5-tri(4-carboxyphenyl)benzene in 3 ml N,N-dimethylformamide, then add 1 ml formic acid and 0.5 ml deionized water, and disperse evenly by ultrasonication to obtain a dispersion. Seal the dispersion and place it in an oven at 130°C for 48 hours. After cooling to room temperature, wash it twice with DMF, wash it once with ethanol, and then dry it to obtain a white powder, recorded as Zr-BTB.
[0052] Zr-BTB@Pt: Weigh 15 mg of Zr-BTB and disperse it in 5 ml of ethanol. Add 300 μl of 10 mg / ml potassium chloroplatinite solution and 1 ml of deionized water and ultrasonically treat for 60 minutes. Then wash with deionized water and ethanol and dry to obtain a gray-black powder recorded as Zr-BTB@Pt.
[0053] Quaternary ammonium salt ligand: 15 g of isonicotinic acid and 26 g of methyl iodide are dissolved in 70 ml of methanol, and the mixture is cooled to room temperature after condensation reflux for 45 hours. A red solid is obtained by filtration, and the solid is washed with acetone until it turns yellow. The quaternary ammonium salt ligand is then purified by recrystallization with methanol. The quaternary ammonium salt ligand is yellow crystals.
[0054] Zr-BTB@Pt-NH4 + : 10 mg Zr-BTB@Pt and 100 mg quaternary ammonium salt ligand were dispersed in 10 ml methanol, condensed and refluxed for 16 hours, cooled to room temperature, washed with methanol and dried to obtain a powder named Zr-BTB@Pt-NH4 + -5.
[0055] Embodiment 6: Zr-BTB: Dissolve 10 mg of anhydrous zirconium oxychloride and 15 mg of 1,3,5-tri(4-carboxyphenyl)benzene in 3 ml of N,N-dimethylformamide, then add 1 ml of formic acid and 0.5 ml of deionized water, and disperse evenly by ultrasonication to obtain a dispersion. Seal the dispersion and place it in an oven at 120°C for 48 hours. After cooling to room temperature, wash it twice with DMF, wash it once with ethanol, and then dry it to obtain a white powder, recorded as Zr-BTB.
[0056] Zr-BTB@Pt: Weigh 15 mg of Zr-BTB and disperse it in 5 ml of ethanol. Add 300 μl of 10 mg / ml potassium chloroplatinite solution and 1 ml of deionized water and ultrasonically treat for 30 minutes. Then wash with deionized water and ethanol and dry to obtain a gray-black powder recorded as Zr-BTB@Pt.
[0057] Quaternary ammonium salt ligand: 15 g of isonicotinic acid and 26 g of methyl iodide were dissolved in 70 ml of methanol, and the mixture was cooled to room temperature after condensation reflux for 40 hours. A red solid was obtained by filtration, and the solid was washed with acetone until it turned yellow. The quaternary ammonium salt ligand was purified by recrystallization with methanol. The quaternary ammonium salt ligand was yellow crystals.
[0058] Zr-BTB@Pt-NH4 + : 10 mg Zr-BTB@Pt and 60 mg quaternary ammonium salt ligand were dispersed in 10 ml methanol, condensed and refluxed for 14 hours, cooled to room temperature, washed with methanol and dried to obtain a powder named Zr-BTB@Pt-NH4 + -6.
[0059] Comparative Example 1 In this comparative example, Zr-BTB@Pt was prepared according to the method of Example 1, and the Zr-BTB@Pt was not modified with a quaternary ammonium salt ligand.
[0060] Photocatalytic hydrogen production experiment The catalysts prepared in the examples and comparative examples were respectively applied to catalytic reactions, and the specific operations were as follows: The photocatalytic reaction was carried out in a 70 ml photocatalytic reactor, and the light source was a xenon lamp with a wavelength of 390 nm to 780 nm.
[0061] 10 mg of tris(2,2'-bipyridyl)ruthenium(II) and 10 mg of the catalysts prepared in the examples and comparative examples were dispersed in 18 ml of acetonitrile, 1 ml of deionized water and 0.5 ml of triethylamine were added to carry out catalytic reaction.
[0062] Result analysis: like Figure 2 As shown, it reflects the hydrogen production efficiency of the photocatalytic reaction of Example 1 and Comparative Example 1; the photocatalytic reaction test shows that Zr-BTB@Pt-NH4 + The photocatalytic hydrogen production efficiency is 4872.1 μmol g −1 h −1 The hydrogen production efficiency of Zr-BTB@Pt photocatalyst without post-modification of quaternary ammonium salt ligands was 2650.5 μmol g −1 h −1 It can be seen that the hydrogen production efficiency of the photocatalytic material is significantly improved by the post-modification method of the charged ligand.
[0063] Comparative Example 1 and Comparative Example 1 show that the photocatalytic hydrogen production efficiency is significantly improved after the quaternary ammonium salt ligand is modified when the active material Pt nanoparticle loading is consistent. Photocatalysis is mainly divided into three processes: one is light excitation, the second is electron-hole separation, and the last is surface reaction. Due to the charged quaternary ammonium salt ligand, it acts as a proton relay in the reaction process, improves the second process of the photocatalytic reaction, accelerates charge transfer, and improves the catalyst efficiency. Secondly, the charged ligand can also accelerate the occurrence of surface reactions, polarize water molecules, and improve the surface reaction rate. The improvement of the photocatalytic hydrogen production efficiency is achieved under the combined action of the two factors.
[0064] like Figure 3 As shown in the figure, it reflects the hydrogen production efficiency of the catalysts prepared in Examples 2-6 in the photocatalytic reaction. The hydrogen production efficiency of Examples 2-6 can reach 4000 μmol g −1 h −1 The above results show that the hydrogen production efficiency of the catalyst prepared in Example 3 for photocatalytic reaction exceeds 10000 μmol g −1 h −1 .
[0065] The endpoints and any values of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, the endpoint values of each scope, the endpoint values of each scope and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.
[0066] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art can still modify or make equivalent substitutions to the specific implementations of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention are within the scope of protection of the claims of the present invention to be approved.
Claims
1. A method for preparing a photocatalyst modified with a charged ligand, characterized in that: include: Add Zr-BTB, potassium chloroplatinite solution and deionized water into ethanol and mix them evenly to react. After the reaction is completed, Zr-BTB@Pt is obtained. Zr-BTB@Pt and quaternary ammonium salt ligands were dispersed in methanol and reacted to obtain Zr-BTB@Pt-NH4 + .
2. The method for preparing a photocatalyst with a charged ligand post-modification according to claim 1, characterized in that: The mass ratio of the Zr-BTB, potassium chloroplatinite and deionized water is 15:(3-9):1000.
3. The method for preparing a photocatalyst with a charged ligand post-modification according to claim 1, characterized in that: The mass ratio of the Zr-BTB@Pt and the quaternary ammonium salt ligand is 1:(6~10).
4. The method for preparing a photocatalyst with a charged ligand post-modification according to claim 1, characterized in that: The Zr-BTB is added to the ethanol, the potassium chloroplatinite solution and the deionized water are mixed evenly to react, and Zr-BTB@Pt is obtained after the reaction is completed. Specifically, Zr-BTB, potassium chloroplatinite solution and deionized water were added to ethanol, and ultrasonic treatment was performed for 30 to 60 minutes to obtain a first product. The first product was washed with deionized water and ethanol and then dried to obtain Zr-BTB@Pt.
5. The method for preparing a photocatalyst with a charged ligand post-modification according to claim 1, characterized in that: The Zr-BTB@Pt and the quaternary ammonium salt ligand are dispersed in methanol and reacted to obtain Zr-BTB@Pt-NH4 + , specifically: Zr-BTB@Pt and quaternary ammonium salt ligands were dispersed in methanol and condensed and refluxed for 12 to 16 hours to obtain a second product. The second product was washed with methanol and dried to obtain Zr-BTB@Pt-NH4 + .
6. The method for preparing a photocatalyst with a charged ligand post-modification according to claim 1, characterized in that: The preparation method of the Zr-BTB is specifically as follows: The zirconium salt and 1,3,5-tri(4-carboxyphenyl)benzene are dissolved in N,N-dimethylformamide, and then formic acid and water are added to the N,N-dimethylformamide, and ultrasonic dispersion is performed to obtain a dispersion, and the dispersion is heated to obtain a third product. After cooling to room temperature, the third product is washed with N,N-dimethylformamide and ethanol, and then dried to obtain Zr-BTB.
7. The method for preparing a photocatalyst with a charged ligand post-modification according to claim 6, characterized in that: The zirconium salt includes zirconium chloride and anhydrous zirconium oxychloride; the mass ratio of the zirconium salt to 1,3,5-tris(4-carboxyphenyl)benzene is 1:(1-1.5); The heating condition is to keep the temperature in an oven at 110° C. to 130° C. for 48 to 60 hours.
8. The method for preparing a photocatalyst with a charged ligand post-modification according to claim 1, characterized in that: The quaternary ammonium salt ligand is prepared by the following method: Dissolve isonicotinic acid and methyl iodide in methanol, condense and reflux for 40 to 48 hours, cool to room temperature, filter to obtain a red solid, wash with acetone until the solid turns yellow, and then recrystallize with methanol to obtain a quaternary ammonium salt ligand; The mass ratio of isonicotinic acid to methyl iodide is 3:(5-6).
9. A photocatalyst modified with a charged ligand obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the charged ligand post-modified photocatalyst according to claim 9 in photocatalytic hydrogen production.
Citation Information
Cited By
Charged ligand post-modified photocatalyst, preparation method therefor and use thereof
WO2026066209A1
